Imperial Feminism in the Yellow Wallpaper by Charlotte Perkins Gilman - Nidhi Chaurasiya; Dr Ravi Kumar Yadav (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Imperial Feminism also known as Colonial feminism is a critical term that analyzes how feminist rhetoric a actions can be used to perpetuate imperialism by framing women’s rights in the service of building the Imperial powers and their empire. The concept emerged from the observation that feminist arguments regarding the rights of women in colonized territories were used to legitimize the imperial rule rather than empowering women in a true sense in terms of education and financial liberty. Charlotte Perkins Gilman, prominent feminist thinker has been often criticized for reflecting the elements of imperial feminism in her works when analyzed particularly in her views on race, eugenics and role of women in society despite her participation in equality and women’s rights. Gilman’s feminism had reflections on a desire for specific homogeneous citizenry due to which women of some other specific groups were totally excluded from her visions of gender equality and these women included non white and non middle class women. The paper attempts to analyze Perkins’ work The Yellow Wallpaper through the lens of Imperial feminism and its implications in the text.